Clinical Study of Different Types of Psoriasis and Homeopathic Management - Mohan, Gundimeda Ram (Homœopathic Links, 2013)
Twenty-five cases of psoriasis of different types were treated. The medicines found to be useful were Calcarea carbonica, Graphites, Natrum muriaticum, Pulsatilla, Arsenicum album, Thuja occidentalis, Sepia, Nitricum acidum, Sulphur and Thyroidinum, as well as the nosodes Tuberculinum, Syphilinum and Carcinosin. Along with treatment, dietetic advice and Psychological counselling were given.
Keywords: Psoriasis